2019
DOI: 10.1017/cem.2019.420
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department referrals from a provincial medical call centre: Is it more than just 1-800-go-to-emerg?

Abstract: ObjectiveHealthLine is Saskatchewan's provincial 24-hour health information and support telephone line. A proportion of HealthLine's callers are referred to the emergency department (ED) for further assessment. The purpose of this study was to gain insight into the appropriateness of these referrals and assess whether they increased the burden on an already strained ED system.MethodsA list of callers referred from HealthLine to Saskatoon EDs from January 1, 2014, to March 31, 2014 was obtained. This list was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“… 23 Community services like HealthLine, a provincial medical call centre, have been shown to positively affect patient urgent care decisions and therefore need to be both consulted and informed regarding UCCs. 52 …”
Section: Resultsmentioning
confidence: 99%
“… 23 Community services like HealthLine, a provincial medical call centre, have been shown to positively affect patient urgent care decisions and therefore need to be both consulted and informed regarding UCCs. 52 …”
Section: Resultsmentioning
confidence: 99%
“…Other studies showed different results regarding the effect of tele-triage systems on the emergency units so some studies suggested that tele-triage interventions led to a moderate to significant decline in non-emergency visits and re-hospitalization, specifically for older and chronic patients and parents with young children. 17 , 18 Still, Turbitt et al stated that patients referred to ED through tele-triage could be potentially managed outside the emergency environment as well. 19 Therefore, tele-triage systems in pandemic situations can be effective in preventing unnecessary visits of patients to ED.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that tele-triage interventions lead to a significant decline in postponing emergency visits and re-hospitalization, especially in older and chronic patients and parents with young children. 17 , 18 Moreover, patients have reported high levels of acceptance and increased satisfaction with tele-triage services. Meanwhile, one study indicated that a large number of the patients referred to ED through tele-triage could have been managed outside the emergency environment as well.…”
Section: Introductionmentioning
confidence: 99%
“…Some published studies demonstrate that teletriage interventions have moderate to substantial reductions of deferrals in ED visits and hospital readmissions, especially for older and chronic patients and parents with young children. 21,[26][27][28] This effect was further demonstrated when teletriage services offered multiple layers of care, such as integrating virtual assessments and appointments by physicians or nurse practitioners. 20 On the contrary, some studies show that a high number of patients with lower urgency conditions are still advised to attend by teletriage professionals.…”
Section: Impact On the Emergency Departmentmentioning
confidence: 99%
“…17,21 This shows that teletriage systems can be effective at deferring patients away from the ED, but there is room for further improvement. 28 Further research is needed to understand the overall impact of teletriage on EDs and the economic impacts on healthcare systems as a whole.…”
Section: Impact On the Emergency Departmentmentioning
confidence: 99%